Penerapan Green Practice pada Bisnis Usaha Kecil Menengah (UKM) Kuliner di Kota Bandung - Meidila Anggita; Natalia Christi; Ignasia Tiffani; Maria Merry Marianti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Small and Medium Enterprises (SMEs) dominate the number of businesses in Indonesia, yet many SME owners are unaware of the importance of implementing green practices in their operations. This study aims to evaluate the implementation of green practices in marketing, operations, and finance within SMEs. The main challenge in adopting a sustainable mindset is the lack of awareness and collaboration between stakeholders for climate change mitigation and adaptation. The proposed solution is to ensure that investments support environmental, social, and governance (ESG) aspects (Otoritas Jasa Keuangan, 2021). The study's findings show that in marketing, Pipinos has adopted eco-friendly packaging, while Nara offers discounts for customers who use their own containers. In terms of finance, both SMEs have not utilized green financing options. Nara is currently applying for a tax relief program from the Environmental Agency for businesses meeting environmental standards. In operations, Pipinos has not optimized energy and water usage, while Nara manages wastewater through a multi-stage treatment process, producing clean water. This research highlights the importance of raising SME owners' awareness of green practices and the need for support from various stakeholders to accelerate sustainable transformation, which is a strategic step in supporting climate change mitigation and environmental sustainability.